1985
DOI: 10.1104/pp.79.4.957
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of the Soluble F1-ATPase of Oat Root Mitochondria

Abstract: The properties of the soluble moiety (F,) of the mitochondrial H'-ATPase from oat roots were examined and compared to those of the native mitochondrial membrane-bound enzyme. The chloroform soluble preparation was purified by Sephadex G-200 and DEAE-cellulose chromatography. The purified F, preparation contained major polypeptides corresponding to a, ,, -y, 6, and e of apparent molecular mass 58, 55, 35, 22, and 14 kilodaltons, respectively. The purified F,-ATPase, like the native enzyme, was inhibited by azi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Although several of these preparations [maize (Zea mays Hack & Leaver, 1983;Partridge et al, 1985), fava bean (Viciafava;Boutry et al, 1983), oat (Avena sativa) root (Randall et al, 1985) and cuckoo-pint (Arum maculatum; Dunn et al, 1985)], like those obtained from mammalian sources, contain five subunits, other preparations contain six subunits [sweet-potato (Ipomoea batatas) root (Iwasaki & Asahi, 1983 pea (Pisum sativum) cotyledon (Horak & Packer, 1985;Horak et al, 1987) and turnip (Brassica napus; O'Rourke, 1988)]. Horak et al (1987) and Kimura et al (1989) have suggested that the additional (sixth) subunit (26-27 kDa) may be equivalent to the oligomycin-sensitivity-conferring protein (OSCP) from bovine heart F1/F0-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…Although several of these preparations [maize (Zea mays Hack & Leaver, 1983;Partridge et al, 1985), fava bean (Viciafava;Boutry et al, 1983), oat (Avena sativa) root (Randall et al, 1985) and cuckoo-pint (Arum maculatum; Dunn et al, 1985)], like those obtained from mammalian sources, contain five subunits, other preparations contain six subunits [sweet-potato (Ipomoea batatas) root (Iwasaki & Asahi, 1983 pea (Pisum sativum) cotyledon (Horak & Packer, 1985;Horak et al, 1987) and turnip (Brassica napus; O'Rourke, 1988)]. Horak et al (1987) and Kimura et al (1989) have suggested that the additional (sixth) subunit (26-27 kDa) may be equivalent to the oligomycin-sensitivity-conferring protein (OSCP) from bovine heart F1/F0-ATPase.…”
Section: Introductionmentioning
confidence: 99%
“…While the enzymes obtained from maize (Zea mays) [1,2], faba bean (Viciafava) [3], oat root (Avena sativa) [4] and cuckoo pint (Arum maculatum) [5], like that from mammalian sources, contain five subunits, those from sweet potato root (lpomoea batatas) [6,7], pea cotyledon (Pisum sativum) [8,9] and turnip (Brassica napus) [10] have six subunits. ATPase subunits in the five subunit preparations are designated on the basis of Lheir mobility in SDS polyacrylamide gel electrophoresis as o~, /3, y, 6, and e with approximate molecular masses of 55000, 52000, 30000, 20000 and 8000 with variations depending on the tissue source.…”
Section: Introductionmentioning
confidence: 99%
“…Little information is available on the plant mitochondrial enzyme while the chloroplast CF,F(, has been isolated and extensively characterized. The mitochondrial F,-ATPase has been purified from diverse plant sources (Boutry et al 1983, Hack and Leaver 1983, Iwasaki and Asahi 1983, Horak and Packer 1985, Dunn et al 1985, Randall et al 1985, Spitsberg et al 1985, Glaser et al 1987. However, none of these reports concerns the isolation of Fi from leaf tissue.…”
mentioning
confidence: 99%